“O futuro é a mulher indígena, ou não será”: uma etnografia das mulheres inỹ karajá do Tocantins no instagram - Souza, Lys Maria Ramos de (Universidade Federal do Tocantins, 2023)
This Course Completion Work addresses the actions and political articulations of Iny Karajá women from Tocantins, through an ethnographic study carried out in the context of the COVID - 19 pandemic. from 2020 to 2022 (years that center the analyzes of this research), made researchers look for new ways to follow their research, as is the case of this work that used netnography, an area of ethnography that seeks to investigate the culture of a certain group or society on social networks, so we use the social network Instagram. Methodological techniques of observation of the profiles of 3 Iny Karajá women on Instagram were also used, followed by interviews and a brief field research in the Iny Karajá territory on Bananal Island/TO in 2022. All these paths pointed out that Iny women are increasingly advancing in spaces of political articulation, often using Iny art to draw the attention of non-indigenous people to their speeches. Among the artistic productions found in the investigation of the narratives, we have the Boneca Ritxoko, for example, which is a Brazilian intangible cultural heritage. The artivism (art + activism) of these women leads us to understand that there are multiverses and multiple forms of power, and this is our main objective to highlight the counter-narratives and cosmopolitics produced in political spaces, or not, that women Iny Karajá women occupy.